Reduced expression of FRG1 facilitates breast cancer progression via GM-CSF/MEK-ERK axis by abating FRG1 mediated transcriptional repression of GM-CSF - Bratati Mukherjee; Ankit Tiwari; Ananya Palo; Niharika Pattnaik; Subrat Samantara; Manjusha Dixit (Cell Death Discovery, 2022)
Abstract Multiple molecular subtypes and distinct clinical outcomes in breast cancer, necessitate specific therapy. Moreover, despite the improvements in breast cancer therapy, it remains the fifth cause of cancer-related deaths, indicating the involvement of unknown genes. To identify novel contributors and molecular subtype independent therapeutic options, we report reduced expression of FRG1 in breast cancer patients, which regulates GM-CSF expression via direct binding to its promoter. Reduction in FRG1 expression enhanced EMT and increased cell proliferation, migration, and invasion, in breast cancer cell lines. Loss of FRG1 increased GM-CSF levels which activated MEK/ERK axis and prevented apoptosis by inhibiting p53 in an ERK-dependent manner. FRG1 depletion in the mouse model increased tumor volume, phospho-ERK, and EMT marker levels. The therapeutic potential of anti-GM-CSF therapy was evident by reduced tumor size, when tumors with decreased FRG1 were treated with anti-GM-CSF mAb. We found an inverse expression pattern of FRG1 and phospho-ERK levels in breast cancer patient tissues, corroborating the in vitro and mouse model-based findings. Our findings first time elucidate the role of FRG1 as a metastatic suppressor of breast cancer by regulating the GM-CSF/MEK-ERK axis.